(untitled) (Zoological Records and Reviews, 2023)
Forest fringe villages – human settlements located immediately adjacent to or embedded within forest landscapes – occupy a critical interface between natural ecosystems and human land use, simultaneously harboring significant vertebrate diversity and representing nodes of human-wildlife conflict and biodiversity loss. Understanding the vertebrate fauna of these interface zones is essential for designing conservation strategies that address both biodiversity protection and the needs of forest-dependent communities. This study presents a comprehensive survey of vertebrate diversity – encompassing mammals, birds, reptiles, and amphibians – in 36 forest fringe villages surrounding the Nagarjunasagar-Srisailam Tiger Reserve (NSTR) in Andhra Pradesh and Telangana, India, using camera trapping, point counts, and visual encounter surveys over two years (2020-2022). A total of 342 vertebrate species are documented across four classes. Camera traps recorded 24 mammal species at village peripheries, including tigers, leopards, and sloth bears within 500 m of habitation. Bird diversity was highest at villages with large trees and traditional grain stores. Human-wildlife conflict incidents – crop raiding by elephants, wild boar, and deer; livestock predation by carnivores; snakebite – are documented at 28 of 36 villages. Forest cover loss rate within 2 km of surveyed villages is quantified from satellite data and correlated with vertebrate species richness decline. An integrated conservation-livelihood framework for NSTR forest fringe villages is proposed.